2016
DOI: 10.3389/fcimb.2016.00148
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Elicited by Oral Immunization of Mice with Salmonella enterica Serovar Typhimurium Braun Lipoprotein (Lpp) and Acetyltransferase (MsbB) Mutants

Abstract: We evaluated the extent of attenuation and immunogenicity of the ΔlppAB and ΔlppAB ΔmsbB mutants of Salmonella enterica serovar Typhimurium when delivered to mice by the oral route. These mutants were deleted either for the Braun lipoprotein genes (lppA and lppB) or in combination with the msbB gene, which encodes an acetyltransferase required for lipid A modification of lipopolysaccharide. Both the mutants were attenuated (100% animal survival) and triggered robust innate and adaptive immune responses. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Moreover, in a mouse that died from infection, there was a marked thrombosis in the spleen and liver, suggesting that this correlates with disease severity. Vaccination can reduce the level of thrombosis induced (109). Furthermore, a model to study Salmonella -associated meningitis demonstrated that this infection can induce thrombosis in the brain (110).…”
Section: Salmonella Infections Of Mice: a Model To Evaluate The Inducmentioning
confidence: 99%
“…Moreover, in a mouse that died from infection, there was a marked thrombosis in the spleen and liver, suggesting that this correlates with disease severity. Vaccination can reduce the level of thrombosis induced (109). Furthermore, a model to study Salmonella -associated meningitis demonstrated that this infection can induce thrombosis in the brain (110).…”
Section: Salmonella Infections Of Mice: a Model To Evaluate The Inducmentioning
confidence: 99%
“…Similarly, in Salmonella enterica serovar Typhimurium, the inactivation of two murein lipoproteins caused a very significant impairment of virulence, in terms of a drastic reduction of invasion/cytotoxicity in cell culture and of mortality in murine models (39) (Table 1). And again, similarly to yersiniae, S. enterica serovar Typhimurium mutants with mutations in some PGN structural elements, such as Braun's lipoprotein, have recently been tested as vaccine candidates, with promising results (40). Interestingly, and still related to Braun's lipoprotein, Hernández and colleagues have shown in Salmonella that the effects of bile could induce the selection of some modifications leading to an increased resistance to this natural detergent (41).…”
Section: Dealing With Cell Wall Structure: Peptidoglycan-associated Lmentioning
confidence: 99%
“…IgA production is important as the first line of defense in intestinal infection. Moreover, Erova et al (2016) showed, using a different vaccination strategy, that the efficiency of IgA against salmonellosis is associated with its sustained production in animal models following vaccination, demonstrating that it also participates in adaptive immunity. We observed a significant increase in IFN-γ levels in animals receiving only one dose of attenuated PT4Δ hupAB , and this profile was sustained at 49 days later after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, live-attenuated vaccines are an attractive vaccine platform as these vaccines can confer long-lasting protection to prevent invasive Salmonella serovars. Moreover, these vaccines are inexpensive and easy-to-implement ( Erova et al, 2016 ). Vaccination protocols for this platform have been tested in both humans ( Maclennan et al, 2014 ) and animals ( Haneda et al, 2011 ; Desin et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%